2014
DOI: 10.4236/health.2014.612188
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Cigarette Smoking and Knowledge of Its Health Implications among Adolescents in Owerri, South-Eastern Nigeria

Abstract: Despite the growing problem of global cigarette use, accurate information on the prevalence and pattern in Nigerian adolescents' remains sparse. The aim of this study was to determine the prevalence of cigarette smoking among in-school male adolescents in Nigerian population and to assess their level of knowledge on the health effects of cigarette smoking. A descriptive cross-sectional study was carried out among 944 randomly selected in-school male adolescents in Owerri, south-east Nigeria, between September … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 8 publications
2
21
0
Order By: Relevance
“…In line with the Global Youth Tobacco Survey (GYTS), our study recorded the highest prevalence of tobacco use among NW zone students . Most previous studies involved students older than 15 years and generally reported a higher prevalence of smokers . This corroborates the tendency of tobacco use to increase with age, as observed in our sample, and underscores the need to target prevention interventions to younger students.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with the Global Youth Tobacco Survey (GYTS), our study recorded the highest prevalence of tobacco use among NW zone students . Most previous studies involved students older than 15 years and generally reported a higher prevalence of smokers . This corroborates the tendency of tobacco use to increase with age, as observed in our sample, and underscores the need to target prevention interventions to younger students.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, while several Nigerian studies have described parental and friends 0 influence on adolescent substance use [8][9][10][11][12][13][14][15][16][17][18][19][20][21], few have investigated personal risk factors (e.g. knowledge, attitudes, and beliefs) and none have investigated risk perceptions and skills.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to other reports 12,15,18,21 . Lower debuting age has also been reported 6,7,10,11,22 .…”
Section: Initiation Agementioning
confidence: 99%
“…In a recent study, it was demonstrated that the knowledge of health problems associated with smoking proved to be the major reason for . It is, therefore, strongly advocated that health education in schools will, to a reasonable extent, reduce the high prevalence of adolescent cigarette smoking in our society 10 .…”
Section: Cessationmentioning
confidence: 99%
See 1 more Smart Citation